2020
DOI: 10.1177/0022034520963710
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Inflammation Primes the Systemic Innate Immune Response

Abstract: The presence of periodontal diseases (PDs) often strongly correlates with other severe chronic inflammatory conditions, including cardiovascular disease, diabetes, and arthritis. However, the mechanisms through which these diseases interact are unclear. In PD, tissue and bone destruction in the mouth is driven by elevated recruitment of polymorphonuclear neutrophils (PMNs), which are primed and recruited from the circulation to sites of inflammation. We predicted that systemic effects on PMN mobilization or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 39 publications
1
76
0
Order By: Relevance
“…The role of the C-Reactive protein in this pathogenesis appears to be one that has strong evidence in its favor [ 14 , 15 ]. A recent study, which used ligature-induced periodontal disease in mouse models and human experimental gingivitis model, demonstrated that periodontal inflammation can result in increased polymorphonuclear neutrophils (PMNs) and potentially prime the systemic innate immune response [ 16 ]. This PMN-mediated hyperinflammatory innate immune response could be the plausible biologic crosslink between periodontal disease and the other chronic inflammatory diseases such as cardiovascular diseases, diabetes and arthritis.…”
Section: The Link Between Periodontal Diseases and Systemic Conditmentioning
confidence: 99%
“…The role of the C-Reactive protein in this pathogenesis appears to be one that has strong evidence in its favor [ 14 , 15 ]. A recent study, which used ligature-induced periodontal disease in mouse models and human experimental gingivitis model, demonstrated that periodontal inflammation can result in increased polymorphonuclear neutrophils (PMNs) and potentially prime the systemic innate immune response [ 16 ]. This PMN-mediated hyperinflammatory innate immune response could be the plausible biologic crosslink between periodontal disease and the other chronic inflammatory diseases such as cardiovascular diseases, diabetes and arthritis.…”
Section: The Link Between Periodontal Diseases and Systemic Conditmentioning
confidence: 99%
“…A multitude of clinical findings demonstrated an unambiguous correlation between periodontitis and systemic diseases, like atherosclerosis, diabetes, and cardiovascular diseases [ 1 ]. The main link between systemic diseases and periodontitis is considered to be the systemic low-grade inflammation (SLGI); apparently a consequence of low-grade endoxemia (LGE) [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 An important mechanism in the progression of periodontal disease is the innate and adaptive inflammatory response after infection by periodontal pathogens. [3][4][5] There are important differences in susceptibility due to inter-individual genetic variants 6 ; for example, genetic variants of IL-37 can affect its expression and immunomodulatory response in relationship with periodontal disease. 7 Besides, a meta-analysis of genetic variations also found that a point mutation in CD14, an actor in innate immune response, is associated with some forms of periodontitis.…”
Section: Introductionmentioning
confidence: 99%